Advantages of different care services for reducing neuropsychiatric symptoms in dementia patients. Issue 4 (7th February 2018) - Suzuki, Yukiko; Kazui, Hiroaki; Yoshiyama, Kenji; Azuma, Shingo; Kanemoto, Hideki; Sato, Shunsuke; Suehiro, Takashi; Ikeda, Manabu
Abstract : Background: It is assumed that care services effectively reduce behavioural and psychological symptoms of dementia (BPSD). However, it is unclear which care services are effective for reducing specific BPSD. The aim of this study was to clarify which care services were recognized by care specialists as being effective for reducing each of 11 BPSD. Methods: We sent unsigned questionnaires to care specialists in Japan. The questionnaires asked specialists to choose from 12 kinds of care services the most, second‐most, and third‐most effective service for reducing each of 11 BPSD. The most effective service was scored as 3 points, the second‐most was 2 points, and the third‐most was 1 point. Specialists were also asked to describe why they chose each service. The 12 kinds of care services were categorized into four categories: (i) home‐visit; (ii) outpatient; (iii) short‐stay; and (iv) facility. Total scores for each category were analyzed using a two‐wayanova . The reasons care specialists chose each service were analyzed using morphological analysis, and representative reasons were extracted. Results: A total of 103 questionnaires were returned. Of the four service categories, outpatient services yielded the highest score for reducing apathy ( P  < 0.001) due to the effectiveness of participating in recreation and receiving stimulation. Facility services yielded the highest score for reducing aberrant motor behaviour ( P  < 0.001). Short‐stay services yielded the lowest score for reducing depression ( P  < 0.001). For eight other kinds of BPSD, there were no significant differences between home‐visit and facility services or between outpatient and facility services. Conclusions: Care specialists reported that effective care services for reducing BPSD differed among types of BPSD. In‐home care services might be effective at reducing many BPSD except for aberrant motor behaviour, suggesting that greater use of in‐home care services might enable people with BPSD to live in their homes for longer.